2021
DOI: 10.1002/app.51738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying polydimethylsiloxane chain length and content on the adhesion and thermal properties of polydimethylsiloxane‐grafted acrylic pressure‐sensitive adhesives

Abstract: Acrylic pressure-sensitive adhesive (acrylic PSA) has advantages such as high adhesion, low cost, and high light transmittance, but it has a low adhesion to low-surface-energy substrates and low thermal stability. To solve these problems, PSA was modified with low surface energy moieties and crosslinked by UV curing. In this study, a polydimethylsiloxane (PDMS) structure with a low surface energy and good thermal properties was introduced into PSA through grafting polymerization to compensate for the disadvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In contrast, no adhesion signal was observed on the force curves of PVA- g 57% -PPDO 9.4 and EVA (Figure A2,A3). To further investigate the adhesion mechanism of the graft copolymer to a smooth or inert surface, the T-peel strength test was carried out for the PVA- g 54% -P­(PDO 7.4 - co -CL 1.4 ) adhesive on the PE surface, which had a relatively low surface energy and thus was regarded hard to be bonded. Notably, the results showed that the T-peel strength of PVA- g 54% -P­(PDO 7.4 - co -CL 1.4 ) to PE (427.0 g f /25 mm) was higher than those of PVA- g 57% -PPDO 9.4 and EVA, which was comparable to the reference values of pressure-sensitive adhesives on low surface energy substrates, indicating that there were strong apolar interactions (van der Waals force, etc.) between PVA- g 54% -P­(PDO 7.4 - co -CL 1.4 ) and the PE surface (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no adhesion signal was observed on the force curves of PVA- g 57% -PPDO 9.4 and EVA (Figure A2,A3). To further investigate the adhesion mechanism of the graft copolymer to a smooth or inert surface, the T-peel strength test was carried out for the PVA- g 54% -P­(PDO 7.4 - co -CL 1.4 ) adhesive on the PE surface, which had a relatively low surface energy and thus was regarded hard to be bonded. Notably, the results showed that the T-peel strength of PVA- g 54% -P­(PDO 7.4 - co -CL 1.4 ) to PE (427.0 g f /25 mm) was higher than those of PVA- g 57% -PPDO 9.4 and EVA, which was comparable to the reference values of pressure-sensitive adhesives on low surface energy substrates, indicating that there were strong apolar interactions (van der Waals force, etc.) between PVA- g 54% -P­(PDO 7.4 - co -CL 1.4 ) and the PE surface (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, the stronger cohesive strength of PVA- g -PPDO than PVA- g -P­(PDO- co -CL) is attributed to the crystallization of PPDO segments. When applied to a smooth or inert surface, owing to the comb-like multibranched topology and strong mobility of the P­(PDO- co -CL) graft chains, a very fine interfacial contact was achieved between the adhesive and adherend, which effectively minimized the adhesive surface energy and resulted in a strong adhesive effect. ,, Comparatively, the PVA- g -PPDO copolymer has a higher crystallinity than PVA- g -P­(PDO- co -CL) because of its homopolymer graft chains (Table S4), which endows the adhesive with improved cohesive strength. Correspondingly, however, the interfacial contact between the adhesive and adherend is weakened.…”
Section: Resultsmentioning
confidence: 99%